Method Development for the Simultaneous Estimation of Etamsylate and Tranexamic Acid by UPLC/Pda in Bulk and Formulation.: Pharmaceutical Science-Pharmacy for Better Health - Mohanrao Tammi setty; Balasekhara Reddy Challa; Srinivasa Babu Puttagunta (International Journal of Life Science and Pharma Research, 2022)
Selective and novel method has been optimized for evaluation of Ethamsylate and Tranexamic acid in bulk, formulation and equipment cleaning samples by UPLC-PDA. The method was developed with the Buffer (pH: 7.0): Acetonitrile, (75:25%, v/v) using the Acquity BEH C18,1.7µ.m,2.1mmX50mm analytical column with analysis time of five minutes. The flow of mobile phase through column was 0.8ml/min.The sample volume was 5 µL. The detection was carried at 260nm in a photodiode array detector. The retention times of Ethamsylate and Tranexamic acid were 1.121 min and 2.122 min respectively. The correlation coefficient (r2) was 0.9997 with linear range of 2.5-30.0 µg/ml for EtamsylateFor Tranexamic acid 5µg/ml-60.0 µg/ml .The correlation coefficient (r2) for Tranexamic acid was found to be 1.000. The LOQ for the Ethamsylate and Tranexamic acid was 25ng/ml and 50ng/ml respectively. The developed method was applied for the bulk,formulation and equipment cleaning samples.The results were found satisfactory.Hence the developed method was proved more accurate and sensitive.It can be used at all the stages in pharmaceutical manufacturing and quality control for evaluating of Ethamsylate and Tranexamic acid.